SUBJECT BODY AND EXPERIENCE IN PHENOMENOLOGICAL PHILOSOPHY - Codruța HAINIC (Studia Universitatis Babeș-Bolyai. Philosophia, 2018)
Applying phenomenological philosophy to psychology means to focus on people’s perception of the world. Ultimately, this revolves around people’s lived experiences. My aim is to identify how philosophical phenomenology can contribute to the development of empirical and hermeneutical methods regarding psychological phenomena. I submit that it does so by analysing the existential dimension and the meaning of human experiences, as they spontaneously occur in the flow of daily life. The first step is to think the body in a subjective way, as a phenomenal, lived body, and to see in what way individual experiences can be linked. Subsequently, I investigate how experiencers occur in space, and show that, unlike things, they must obtain access to space and to self-localization in space in order to be experientially in it.